Some contributions to the theory of generalized Orlicz sequence space - Jebril, Iqbal H.; Reddy, B. Surender; Dutta, Hemen (Tamsui Oxford Journal of Mathematical Sciences)
A description of the Orlicz difference sequence space ℓ M (Δ (m) ) generated by an Orlicz function M and a new generalized difference operator Δ (m) is presented. We investigate some topological structures relevant to this space. It is also shown that under certain conditions ℓ M (Δ (m) ) is topologically isomorphic to ℓ ∞ . Furthermore we define a subspace h M (Δ (m) ) of ℓ M (Δ (m) ) and it is shown that under certain conditions h M (Δ (m) ) is topologically isomorphic to c 0 .